A Comparative Study of Phytoplankton Communities and Eutrophication Status in Two Urban Ponds Within Dhaka Metropolis (Dhaka University Journal of Biological Sciences, 2024)
Changes in physicochemical water quality and plankton biomass over time can clearly indicate the eutrophication status of a water body. Urban ponds are particularly susceptible to cultural and natural eutrophication, making it essential to study their water quality and phytoplankton biomass. This study examined two urban ponds within the University of Dhaka campus: Shahidullah Hall Pond (SH-pond) and Museum Pond (Mu-pond). Common phytoplankton in both ponds included species like Pediastrum simplex, Melosira granulata var. angustata, Synedra nana, Ceratium sp., and Ceratium furcoides, along with zooplankton such as Brachionus sp., Keratella cochlearis, and copepod nauplii. The higher diversity of zooplankton compared to phytoplankton suggests that zooplankton overgrazing has reduced phytoplankton species composition. The study’s results indicate a clear trend of eutrophication in both ponds. Over three decades, SH-pond showed increases in water temperature (4.5°C), alkalinity (0.32 meq/L), dissolved oxygen (6.84 mg/L), soluble reactive phosphorus (21.35 μg/L), nitrate (137.77 μg/L), and chlorophyll-a (23.76 μg/L), with water transparency decreasing by 67 cm. Eutrophication indicators like dissolved oxygen, nitrogen, phosphorus, and phytoplankton biomass (chlorophyll-a) increased by 1.9, 1.82, 2.23, and 2.21 times, respectively, suggesting significant eutrophication in Sh-pond. In contrast, over 26 years, Mu-pond data showed decreases in water temperature (2.66°C), pH (0.18), conductivity (31 μS/cm), silica (12.17 mg/L), and chlorophyll-a (12.4 μg/L), but increases in dissolved oxygen (7.61 mg/L), soluble reactive phosphorus (1.16 μg/L), and nitrate nitrogen (170.75 μg/L). This suggests a slower rate of eutrophication in Mu-pond. Human intervention is a critical factor influencing eutrophication in urban ponds, highlighting the need for effective management systems.Dhaka Univ. J. Biol. Sci. 33(2): 15-26, 2024 (July)